Kinetic study on the heterogeneous degradation of coniferyl alcohol by OH radicals - Liu, Changgeng; He, Yucan; Chen, Xiao’e (Chemosphere (Oxford), 2020)
Coniferyl alcohol derived from lignin pyrolysis, is a potential tracer for wood burning emissions, but its atmospheric stability toward OH radicals is not well known. In this work, the degradation kinetics of coniferyl alcohol by OH radicals was studied using a flow reactor at different OH concentrations, temperatures, and relative humidity (RH). The results showed that coniferyl alcohol could be degraded effectively by OH radials, and the average second-order rate constant (k2) was (11.6 ± 0.5) × 10−12 cm3 molecule−1 s−1 at the temperature and RH of 25 °C and 40%, respectively. Additionally, increasing temperature facilitated the degradation of coniferyl alcohol and the Arrhenius equation could be expressed as k2 = (1.7 ± 0.3) × 10−9exp [-(1480.2 ± 55.6)/T] at 40% RH. Meanwhile, increasing RH had a negative impact on the degradation of coniferyl alcohol. According to the k2 obtained under different conditions, the atmospheric lifetime of coniferyl alcohol was in the range of 13.5 ± 0.4 h to 22.9 ± 1.4 h. The results suggested that the atmosphere lifetime of coniferyl alcohol was predominantly controlled by OH radicals. [Display omitted] •Degradation kinetics of coniferyl alcohol by OH radicals was studied.•High temperature and low RH facilitated the degradation of coniferyl alcohol.•OH radicals play a dominant role in the degradation of coniferyl alcohol.